CFD simulations of two opposing plane wall jets in a generic empty airplane cabin: Comparison of RANS and LES. (November 2021) - Thysen, J-H.; van Hooff, T.; Blocken, B.; van Heijst, G.J.F.
Abstract: Accurate computational fluid dynamics (CFD) simulations of the ventilation flow in airplane cabins are important for ventilation design optimisation regarding passenger health, thermal comfort and energy efficiency. The complex unsteady flow phenomena inside the cabin are challenging in numerical modelling and therefore dedicated validation of the simulation outcomes is required. The majority of airplane ventilation studies performed steady Reynolds-averaged Navier-Stokes (RANS) simulations and focused mainly on global flow field characteristics. This paper presents both steady RANS and transient simulations, including unsteady RANS and large eddy simulations (LES), of the flow driven by opposing plane wall jets in a reduced-scale isothermal water-filled generic airplane cabin. A detailed analysis of the mean velocity and turbulence characteristics (including Reynolds stresses) of the cabin flow is outlined, encompassing a thorough investigation of the fundamental flow components such as the opposing jets and the merged jet. Specific attention is devoted to LES grid sensitivity and the performance of different RANS turbulence and LES subgrid-scale (SGS) models is assessed by comparison with particle image velocimetry (PIV) measurements. It is shown that LES in general performs much better than RANS, the latter being incapable of providing accurate mean flow characteristics within the interaction zone and merged jet due to the underlying dynamic opposing jet interaction. Unsteady RANS partly covers the unsteadiness, however, turbulence levels remain systematically underpredicted and LES is required for a correct representation. Differences between the LES SGS model predictions are limited to the SGS kinetic energy budget of the total turbulent kinetic energy. Graphical abstract: Image 1 Highlights: CFD simulations of mixing ventilation with opposing wall jets in a generic cabin. Validation of mean velocity and turbulence data with PIV measurements. Mean characteristics of global flow field, supply jets and merged jet. Performance of different RANS turbulence and LES subgrid-scale models. RANS fails to correctly predict mean flow characteristics in jet interaction zone.